ANTI-RACISM THROUGH IMAGES: STUDY OF THE PEDAGOGICAL DIDACTIC MATERIAL OF THE MUNICIPAL EDUCATION NETWORK OF SANTO ESTEVÃO-BA - Smigura, Marcela Souza Macedo; Paulo, Glaucia Maria Costa Trinchão (Seven Editora, 2024)
In this text, the analysis of an image is presented, in this specific case, a comic strip that brings the discussion about the myth of reverse racism, it is part of the notebook of remote activities for elementary school final years (6th to 9th grade) in the municipality of Santo Estevão-Ba, specifically the edition notebook 3 The face of Racism in Brazil. These notebooks considered by the municipal school network of Santo Estevão-Ba, as a pedagogical didactic material, are objects of research by the author in the academic master's degree in education at the State University of Feira de Santana.The object of analysis of this text is a comic strip that contains a dialogue between young people, the girl Niara, created by the cartoonist Aroeira, has been bringing a dialogue where the questioning of reverse racism appears.As an imagetic resource, the comic strip analyzed has a discursive potential when dealing with the racial theme, as a paradox, a contradiction, using a sarcastic message in the content of the phrase "reverse racism there" [...], a simple and provocative reading for the student's understanding. The comic strip analyzed as an image demonstrates the intrinsic relationship between Education and Drawing, which should be valued in the field of didactic materials, and its discursiveness. DOI:https://doi.org/10.56238/sevened2024.037-086